Atmospheric responses over Asia to sea ice loss in the Barents and Kara seas in mid–late winter and early spring: a perspective revealed from CMIP5 data - Zhe, Han; Shuanglin, Li (Polar Research Institute of China - PRIC, 2020)
This study investigated atmospheric responses in mid–late winter and early spring to sea ice loss in the Barents and Kara seas using regressions of the January–March mean atmosphere on Barents and Kara sea ice area in November and December. Similar atmospheric circulation responses were obtained from reanalysis data and multimodel ensemble results from the Coupled Model Intercomparison Project Phase 5, i.e., sea ice anomalies are the dominant factor driving the overlying atmosphere. The results showed that an Arctic–Asia dipole structure, with opposite anomalies over the mid-latitudes of Asia and over the adjoining Arctic, appears to be the key atmospheric circulation anomaly influencing the East Asian climate in mid–late winter and early spring.